Ab initio simulations on charged interstitial oxygen migration in corundum - Platonenko, Alexander; Gryaznov, Denis; Zhukovskii, Yuri F.; Kotomin, Eugene A. (Elsevier B.V., 2018)
We have calculated possible migration trajectories for single-charged interstitial Oi− anion using large-scale hybrid density functional theory within linear combination of atomic orbitals approach to defective α-Al2O3 crystals. The most energetically favorable configuration for charged Oi− anion is formation of pseudo-dumbbell (split interstitial) with a regular Oreg ion. For charged interstitial oxygen migration, the energy barrier turns out to be ∼0.8–1.0 eV. This is considerably smaller than that for a neutral interstitial atoms (1.3 eV), in agreement with experimental data.
We have performed this work within the framework of the EUROfusion Consortium receiving funding from the European grant agreement 633053. The views and opinions expressed herein do not necessarily reflect those of the European Commission. Authors thank R. Vila, A.I. Popov, A. Luchshik and R.A. Evarestov for fruitful discussions. To carry out large-scale calculations, we have used the HPC supercomputer at Stuttgart University (Germany)
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; α-Al2O3(corundum, sapphire); Charged oxygen interstitial diffusion; Hybrid DFT-LCAO calculations